Effect of drying on the viscoelastic response of a dual-crosslinked PVA hydrogel. (September 2021) - Cui, Fan; Wang, Jikun; Zehnder, Alan; Hui, Chung-Yuen
Abstract: The effect of drying on the viscoelastic, tensile behavior of a dual cross-linked poly(vinyl alcohol)(PVA) hydrogel is studied experimentally. This gel contains about 90% water when fully hydrated and is highly stretchable. Using a microbalance with a density kit it is found that as the gel dries its volume shrinks in linear proportion to the mass. The impact of drying on the gel's mechanical properties is measured in uniaxial tension tests, which include loading–unloading tests at three different stretch rates, a complex loading history test consisting of two different loading segments and a stress-relaxation test. The resulting data show that the gel becomes much stiffer as the gel dries and that drier gels do not fully recover upon unloading. The viscoelastic response from specimens with different hydration levels can be described by a previously developed constitutive model of the gel. The results show that the constitutive model parameters are strongly dependent on hydration level.